Hubungan Kualitas Tidur dengan Tingkat Prestasi Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Made Fernanda Arya Dharma; I Made Pariartha; Ni Wayan Diana Ekayani (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[The Relationship between Sleep Quality and Student Achievement Level of the Faculty of Medicine and Health Sciences, Warmadewa University] Medical students have a higher prevalence rate of poor sleep quality than the rest of the student population. The existence of abnormal sleep times can be related to academic stress. Seeing the large influence of a person's sleep quality on academic achievement, it is therefore necessary to conduct a study that examines this condition in a more specific scope, such as at the Faculty of Medicine and Health Sciences, Warmadewa University. The purpose of this study was to determine the relationship between sleep quality and achievement levels of FKIK Warmadewa University students in 2019, 2020 and 2021. This research is an analytical study using a Cross Sectional Study design. Data collection was carried out using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The data will then be analyzed using the SPSS application with the Spearman Rank correlation statistical test method. The results of the study illustrate that the quality of sleep in each class is dominated by poor sleep quality with details of 65.6% in the 2019 class, 75.4% in the 2020 class and 73.7% in the 2021 class. The student achievement level in the 2019 class is dominated by excellent indicators (56 .6%), class of 2020 with excellent indicators (60.8%), and class of 2021 with very good indicators (71.8%). The results of the correlation analysis stated that there was a significant positive correlation between the two variables in the 2019 class (r = 0.242; p<0.01), 2020 (r = 0.247; p<0.01), and 2021 (r = 0.216; p<0.01).